SPACs with focus on China - Yochanan Shachmurove; Milos Vulanovic (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
In this study, we examine characteristics of Specified Purpose Acquisition Companies (SPACs) used as a financing tool for companies from China in period 2004-2011. We offer the evidence that, similarly to evidence from studies on reverse mergers focusing on China, SPACs that focus on China are not different in their characteristics from other SPACs. We test for the performance of the SPACs focused on China and show that their performance is not inferior to the performance of other SPACs. On the contrary, an investment in the equally weighted portfolio of SPACs with focus on China provides higher absolute return than an investment in the equally weighted portfolio of other SPACs. This evidence establishes that, on average, SPACs focused on China are as equally a valid investment choice as any other SPAC.
Keywords: G12; G14; G24; G30; G32; G34; 330; SPAC; Specified Purpose Acquisition Companies; China; Blank Checks